Sub-lethal combined effects of illicit drug and decreased pH on marine mussels: A short-time exposure to crack cocaine in CO2 enrichment scenarios - da Silva Souza, Lorena; Bonnail, Estefanía; Maranho, Luciane Alves; Pusceddu, Fabio Hermes; Cortez, Fernando Sanzi; Cesar, Augusto; Ribeiro, Daniel Araki; Riba, Inmaculada; de Souza Abessa, Denis M. [UNESP]; DelValls, Ángel; Pereira, Camilo Dias Seabra (Elsevier, 2021)
The increasing CO2-concentrations in the atmosphere promote ocean acidification. Seawater chemistry changes interact with contaminants, such as illicit drugs in the coastal zones. This work evaluates impacts of pH decrease and crack-cocaine exposure on the commercial mussel Perna perna through biomarker responses (lysosomal membrane stability, lipid peroxidation, and DNA strand breaks). The organisms were exposed to different crack-cocaine concentrations (0.5, 5.0, and 50 μg L−1) combined with different pH values (8.3, 8.0, 7.5, 7.0, 6.5, and 6.0) for 96 h. Crack-cocaine in the different acidification scenarios triggered cyto-genotoxicity, which affected the overall health of mussels exposed to cocaine environmentally relevant concentration. This study produced the first data on biomarker responses associated with CO2-induced acidification and illicit drugs (crack-cocaine) in marine organisms.
Keywords: Biomarkers; CO2 enrichment; Crack cocaine; Marine mussel; Ocean acidification